Laparoscopic versus Open Inguinal Hernia Repair Is Feasible in Infants with Caudal Anesthesia and Spontaneous Respiration - Kiblawi, Rim; Beck, Christiane; Keil, Oliver; Schukfeh, Nagoud; Hofmann, Alejandro Daniel; Ure, Benno Manfred; Kuebler, Joachim Friedrich (European Journal of Pediatric Surgery, 2022)
Introduction Minimally invasive surgery (i.e., laparoscopy) and minimally invasive anesthesia (i.e., caudal anesthesia with spontaneous respiration) have separately shown benefits for inguinal hernia repair in infants, yet to what degree these techniques can be combined remains unknown. This study investigated whether laparoscopy impacts the feasibility of performing caudal anesthesia with spontaneous respiration in infants.Methods Prospectively collected data of all infants less than 12 months old and over 3 kg weight who underwent laparoscopic indirect hernia repair (LAP) at our department from 2019 to 2021 were compared with a historical control-matched group of infants who underwent open repair (OPEN) from 2017 to 2021. We assessed the patients' characteristics, anesthesia, and surgical data as well as intra- and postoperative complications.Results A total of 87 infants were included (LAP n = 29, OPEN n = 58). Caudal anesthesia with spontaneous respiration was feasible in 62.1% of cases (LAP n = 55.2%, OPEN n = 65.5%; nonsignificant). Neither group registered anesthetic intra- or postoperative complications. Sedatives were utilized in 97% of LAP patients versus 56.9% of OPEN patients (p < 0.00001). The airway was secured with a laryngeal mask in 89.7% of patients during LAP versus 41.4% during OPEN (p < 0.00001). No significant differences were found regarding the use frequency of opioids (48.3% LAP vs. 34.5% OPEN; nonsignificant) or neuromuscular blockers (6.9% LAP vs. 5.2% OPEN; nonsignificant).Conclusion This is the first comparative study on caudal anesthesia and spontaneous respiration in infants undergoing laparoscopic versus open inguinal hernia surgery. Laparoscopy increased the need for ventilatory support and sedatives but did not significantly impair the feasibility of caudal anesthesia and spontaneous respiration.
Keywords: laparoscopic inguinal hernia repair; infants; caudal anesthesia; spontaneous respiration; minimally invasive surgery